Consumption of vitamins and minerals before and during a pandemic of COVID-19 - Popović Milenković, Marija; Tomović, Marina (Archives of Pharmacy, 2022)
Food supplements (FS) are concentrated sources of vitamins, minerals, or other ingredients with nutritional or other physiological effects. Due to their easy availability, their consumption has increased. The aim of this research is comparison of supplement consumption in the period before and the period during the COVID pandemic. Pharmacy level research was done. We observed the amount of issued supplements for each quarter in 2019 and compared these results with the amount of issued supplements in COVID-19’ waves from March 2021 to March 2022. Observed supplements contain vitamins (C, D, B12), minerals (Ca, Mg, Zn, Se, Fe), alpha lipoic acid, glucosamine, chondroitin and collagen. Research showed that the consumption of vitamins C, D and Mg, Zn, Se and alpha lipoic acid has significantly increased in comparison to the period before the pandemic. At the beginning of the pandemic, the consumption of alpha lipoic acid has increased 2.7 times, and later 150-200 times. Vitamin D consumption has increased 2.4 times, and later 7-9 times. Vitamin C and Zn consumption has increased 2 times, and later 20 times. Vitamin B12 consumption was at the same level, and Mg consumption had a slight increase. Ca and Fe consumption was reduced 2 times and glucosamine, chondroitin and collagen consumption was reduced up to 5 times. This data has shown us that patients have focused their interest and finances on the immunity, and other conditions were partially or completely neglected.